HIV sero-status disclosure and associated factors among HIV positive women in East Africa: Systematic review and meta-analysis. Implications for prevention of mother-to-child HIV transmission - Mosisa, Getu; Mulisa, Diriba; Oluma, Adugna; Bayisa, Lami; Merdassa, Emiru; Bayisa, Diriba; Tamiru, Afework; Tolossa, Tadesse; Chala Diriba, Dereje; Fetensa, Getahun; Wakuma, Bizuneh (Frontiers in Public Health, 2022)
Background Women's HIV-positive disclosure plays a pivotal role to achieve the goal of preventing mother-to-child transmission (PMTCT) among pregnant women in particular. Although several primary studies were conducted in the different countries of East Africa, no study concluded the prevalence of women's HIV status disclosure and associated factors in East Africa. Therefore, the current study aimed to assess the pooled prevalence of disclosure status and associated factors among women in East Africa. Objectives To assess the pooled prevalence of HIV sero-status disclosure and associated factors among women in East Africa. Methods HINARI, PubMed, and Cochrane Library databases were searched. The data were extracted using a Microsoft Excel spreadsheet and STATA v 14.1 was used for the analysis. The Funnel plots and Egger's statistical test was used to check publication bias. Heterogeneity was assessed by conducting sensitivity and subgroup analyses. Result The pooled prevalence of sero-status disclosure among women in East Africa was 73.77% (95%CI 67.76, 79.77). Knowing partner's sero-status (OR = 10.04(95%CI 3.36, 31.84), married (OR = 2.46 (95%CI 1.23, 4.89), smooth relationship (OR = 3.30 (95%CI 1.39, 7.84), and discussion on HIV before the test (OR = 6.96 (95%CI 3.21, 15.05) were identified determinants of HIV sero-status disclosure. Conclusion The current systematic and meta-analysis revealed that nearly one-fourth of women had not disclosed HIV sero-status to at least one individual. Knowing the partner's HIV sero-status, being married, having a smooth relationship, and discussing on HIV before the test were determinants of disclosure status. Therefore, disclosure of HIV-positive sero-status among women living with HIV needs to be strengthened.